2019
DOI: 10.1021/acs.analchem.9b04176
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Nondestructive Rare Earth Element Detection by Means of Wavelength-Dispersive X-ray Fluorescence Spectroscopy Enabled by an Energy Dispersive pn-Charge-Coupled-Device Detector

Abstract: Detection of rare earth elements (REE) is commonly performed with destructive techniques such as (LA)-ICP-MS or coupled to a destructive sample preparation. When investigating unique geological samples, such as cometary, asteroidal or interstellar material from sample return missions or inclusions in deep-Earth diamonds, a non-destructive method is preferred. The presented non-destructive highly sensitive wavelength-dispersive X-ray fluorescence spectroscopy (WD-XRF) technique is designed to measure the L-line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Basic identification of mineral inclusions is often straightforward, especially by referring to the spectra of those minerals that have been found previously in diamond, or even those that are anticipated to occur in the deep mantle based on high-pressure experiments (Smith 2021). When used in conjunction with techniques to measure inclusion composition, such as EPMA analysis, or in situ with synchrotron-XRF (Laforce et al 2014;De Pauw et al 2020), Raman spectroscopy provides a simple way to confirm the crystal structure of mineral phases. The technique can also reveal hidden phases that might otherwise go unnoticed, such as molybdenite in sulfide inclusions (Kemppinen et al 2018), or invisible layers of fluid trapped at the interface between solid inclusions and the host diamond (e.g., Nimis et al 2016;Smith et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Basic identification of mineral inclusions is often straightforward, especially by referring to the spectra of those minerals that have been found previously in diamond, or even those that are anticipated to occur in the deep mantle based on high-pressure experiments (Smith 2021). When used in conjunction with techniques to measure inclusion composition, such as EPMA analysis, or in situ with synchrotron-XRF (Laforce et al 2014;De Pauw et al 2020), Raman spectroscopy provides a simple way to confirm the crystal structure of mineral phases. The technique can also reveal hidden phases that might otherwise go unnoticed, such as molybdenite in sulfide inclusions (Kemppinen et al 2018), or invisible layers of fluid trapped at the interface between solid inclusions and the host diamond (e.g., Nimis et al 2016;Smith et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…De Pauw et al 38 demonstrated a high-resolution method for the non-destructive detection of REEs . The characteristic X-rays emitted by the sample were dispersed by a fixed Ge(111) analyser crystal over the active area of a pnCCD detector thereby enabling the high-energy-resolution detection of X-rays differentiated by their corresponding Bragg angles.…”
Section: Synchrotron and Large Scale Facilitiesmentioning
confidence: 99%
“…The common used analytical methods for rare earth elements are neutron activation analysis (NAA), 9 inductively coupled plasma emission spectrometry (ICP-OES), 10 inductively coupled plasma mass spectrometry (ICP-MS) 11,12 and X-ray uorescence spectrometry (XRF), 13 etc. However, the above methods have more or less disadvantages.…”
Section: Introductionmentioning
confidence: 99%